Piezoresistive Multi-Walled Carbon Nanotube/Epoxy Strain Sensor with Pattern Design - Hwang, Mun-Young (Materials (Basel), 2019)
Carbon nanotube/polymer-based composites have led to studies that enable the realization of low-cost, high-sensitivity piezoresistive strain sensors. This study investigated the characteristics of piezoresistive multi-walled carbon nanotube (MWCNT)/epoxy composite strain sensors subjected to tensile and compressive loads in one direction at relatively small amounts of strain. A patterned sensor was designed to overcome the disadvantage of the load direction sensitivity differences in the existing sensors. The dispersion state of the MWCNTs in the epoxy polymer matrix with the proposed dispersion process was verified by scanning electron microscopy. An MWCNT/epoxy patterned strain sensor and a patch-type strain sensor were directly attached to an acrylic cantilever beam on the opposite side of a commercial metallic strain gauge. The proposed patterned sensor had gauge factors of 2.52 in the tension direction and 2.47 in the compression direction. The measured gauge factor difference for the patterned sensor was less than that for the conventional patch-type sensor. Moreover, the free-vibration frequency response characteristics were compared with those of metal strain gauges to verify the proposed patch-type sensor. The designed drive circuit compensated for the disadvantages due to the high drive voltage, and it was confirmed that the proposed sensor had higher sensitivity than the metallic strain gauge. In addition, the hysteresis of the temperature characteristics of the proposed sensor is presented to show its temperature range. It was verified that the patterned sensor developed through various studies could be applied as a strain sensor for structural health monitoring.